2015
DOI: 10.1152/jn.00614.2014
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine enhances inhibition of mouse vagal motor neurons by modulating excitability of premotor GABAergic neurons in the nucleus tractus solitarii

Abstract: The caudal nucleus of the solitary tract (NTS) serves as the site of the first synapse for visceral sensory inputs to the central nervous system. The NTS sends functional projections to multiple brain nuclei, with gastric-related projections primarily targeting the dorsal motor nucleus of the vagus (DMV). Previous studies have demonstrated that the majority of caudal NTS neurons that project to the DMV respond robustly to nicotine and express nicotinic acetylcholine receptors (nAChRs). However, the cytochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, GABA is the major inhibitory transmitter in the brain. Studies by Xu et al showed that nicotinic acetylcholine receptors (nAChRs) activate GABAergic neurons in the tail of the NTS and enhance the inhibition of mouse vagal motor neurons [29]. Previous studies have shown that the microinjection of nonselective ionotropic glutamate receptor antagonist canine uridine into the dorsal vagus complex (i.e., NTS, DMV, and AP) has little effect on gastric motility, whereas microinjection of the GABAA antagonist bicuculline increases gastric motility [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GABA is the major inhibitory transmitter in the brain. Studies by Xu et al showed that nicotinic acetylcholine receptors (nAChRs) activate GABAergic neurons in the tail of the NTS and enhance the inhibition of mouse vagal motor neurons [29]. Previous studies have shown that the microinjection of nonselective ionotropic glutamate receptor antagonist canine uridine into the dorsal vagus complex (i.e., NTS, DMV, and AP) has little effect on gastric motility, whereas microinjection of the GABAA antagonist bicuculline increases gastric motility [30].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that nicotine has broad effects on non-CA neurons, suggesting a wide influence of nicotine on NTS function. Our response rate is higher than that reported for neurons in the rat NTS (48,87), as well as among mouse NTS GABAergic neurons projecting to the dorsal motor nucleus of the vagus (DMNV) (101). The variance may reflect differences in slice preparation, since we use a horizontal brain slice as opposed to a coronal slice, and may therefore record from slightly different regions of the NTS.…”
Section: Discussionmentioning
confidence: 57%
“…Nicotine preferentially activates DMNV-projecting NTS neurons compared with those that project to the parabrachial nucleus (27). NTS-CA neurons have been shown to project to both regions (8,79,80) and presumably represent some of the nicotinesensitive neurons in both groups, in addition to the GABA neurons identified by Xu et al (101).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations